2016
DOI: 10.1111/rode.12175
|View full text |Cite
|
Sign up to set email alerts
|

Brazil and China: Two Routes of Economic Development?

Abstract: We look at two emerging economies, Brazil and China, and propose an evaluation of their recent development in terms of growth performance and the evolution of income inequality. Our analysis, therefore, is related to the literature on their recent vast growth and also to the much debated Kuznets curve and theory. However, we claim that neither the growth nor the Kuznets approach capture recent relevant phenomena characterizing such countries' dynamics: namely, the presence of at least two distinct growth model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
1
7
0
1
Order By: Relevance
“…For the Uruguayan case, the results showed a negative linear relationship between income distribution and economic growth in the long-run. Similar long-run relationships are found in Mexico (Risso et al, 2013), Brazil (Policardo et al, 2015) and Portugal (Andrade et al, 2014). However, differences across studies are found in relation to the causality between inequality and economic growth.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…For the Uruguayan case, the results showed a negative linear relationship between income distribution and economic growth in the long-run. Similar long-run relationships are found in Mexico (Risso et al, 2013), Brazil (Policardo et al, 2015) and Portugal (Andrade et al, 2014). However, differences across studies are found in relation to the causality between inequality and economic growth.…”
Section: Discussionsupporting
confidence: 60%
“…Causality is found to go from economic growth to inequality in the Uruguayan and Mexican cases. Conversely, for Brazil and Portugal, inequality causes economic growth (Policardo et al, 2015;and Andrade et al, 2014;respectively). A positive relationship between inequality and growth for the pre and post reforms periods is found in China, and causality goes from inequality to growth in the pre-reform period (Risso and Sánchez-Carrera, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En esta misma línea, se encuentran algunos resultados de estudios que realizan su análisis sobre un sólo país, en los casos de México y Uruguay por ejemplo, se encuentra relación negativa entre las variables (Risso, Punzo y Sánches Carrera, 2013;Brida, Lanzilotta y Méndez, 2017). Otros estudios en cambio, encuentran que para este tipo de países la relación no es significativa (Perroti, 1996;Barro, 2000), mientras que algunos trabajos concluyen que la relación tiene forma de U o U invertida (Bengoa y Robles, 2005;Policardo, Punzo y Sánchez Carrera, 2016). Para los países desarrollados o de alto ingreso, son varios los trabajos que encuentran una relación positiva entre crecimiento y desigualdad (Forbes 2000;Barro, 2000;Voitchovsky, 2005;Bengoa y Robles, 2005;Castelló, 2010).…”
Section: Revisión De La Literaturaunclassified